Improving The Performance Of Wireless Sensor Network With Multi Factor Strategies - et. al., Venkateswara Rao M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the design of wireless sensor network (WSN), packet delivery ratio(PDR) is an import parameter to be maximized. PDR plays an important role for improving the performance of WSN. With the existing schemes, a secure zone-based routing protocol was implemented for life time improvement in WSNs. In multi - hop communication, a new routing criterion was formulated for packet transmission. Security against message tampering, dropping and flooding attacks were incorporated in the routing metric. The approach skipped risky zones as a whole from routing and choose alternative path to route a packet in secured manner with less energy consumption. Though energy conservation and attack resilience are achieved, congestion in WSN is increased and because of it packet delivery ratio is diminished. To address this problem, we propose a solution to improve the packet delivery ratio with a multi factor strategy involving routing, differentiation of flows, flow-based congestion control with retransmission and redundant packet coding. Detailed analysis and simulations are undertaken to evaluate the efficiency of the contemplated work compared to the existing solutions.